The Maternal Infant Microbiome: Considerations for Labor and Birth. Issue 6 (November 2017) - Dunn, Alexis B.; Jordan, Sheila; Baker, Brenda J.; Carlson, Nicole S.
Abstract : Abstract: The human microbiome plays a role in maintaining health, but is also thought to attenuate and exacerbate risk factors for adverse maternal–child health outcomes. The development of the microbiome begins in utero; however, factors related to the labor and birth environment have been shown to influence the initial colonization process of the newborn microbiome. This "seeding" or transfer of microbes from the mother to newborn may serve as an early inoculation process with implications for the long-term health outcomes of newborns. Studies have shown that there are distinct differences in the microbiome profiles of newborns born vaginally compared with those born by cesarean. Antibiotic exposure has been shown to alter the microbial profiles of women and may influence the gut microbial profiles of their newborns. Considering that the first major microbial colonization occurs at birth, it is essential that labor and birth nurses be aware of factors that may alter the composition of the microbiome during the labor and birth process. The implications of various activities and factors unique to the labor and birth environment that may influence the microbiome of women and newborns during the labor and birth process (e.g., route of birth, antibiotic use, nursing procedures) are presented with a focus on the role of labor nurses and the potential influence of nursing activities on this process. Abstract : Multiple aspects of the labor and birth environment have been shown to influence the initial colonization process of the newborn microbiome. Implications of various nursing activities and factors unique to the labor and birth environment that may influence the microbiome of women and newborns during labor and birth are presented.